2000
DOI: 10.1046/j.1365-2664.2000.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surgically imposed sterility on free‐ranging rabbit populations

Abstract: Summary1. Demographic changes in response to surgically imposed female sterility were monitored in 12 free-ranging rabbit populations in south-western Australia over a 4-year period. This was part of a research programme aimed at examining the potential for virally vectored immunocontraception to limit the abundance of rabbits (e.g. using a recombinant myxoma virus) and other mammalian pests. Sterility levels were 0%, 40%, 60% and 80% of all females in year 1, with a similar proportion of female recruits steri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
50
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 41 publications
(74 reference statements)
7
50
1
Order By: Relevance
“…For example, sterilised feral Soay rams showed increased food consumption and survival compared with control rams, ultimately leading to increased animal numbers and impact on the plant community (Jewell 1986). PZP-based immunocontraceptives increased lifespan and body conditions of mares Kirkpatrick and Turner 2007), tubal ligation increased survival in rabbits (Twigg et al 2000;Williams et al 2007) and GonaCon improved body condition of deer (Gionfriddo et al 2011b). Conversely, Saunders et al (2002) observed no differences in survival, dispersal or territory size of surgically sterilised foxes compared with fertile foxes, although sterilised vixens were more likely than fertile females to share their territories with each other.…”
Section: Fertility-control Impact On Wildlife Populationsmentioning
confidence: 85%
See 3 more Smart Citations
“…For example, sterilised feral Soay rams showed increased food consumption and survival compared with control rams, ultimately leading to increased animal numbers and impact on the plant community (Jewell 1986). PZP-based immunocontraceptives increased lifespan and body conditions of mares Kirkpatrick and Turner 2007), tubal ligation increased survival in rabbits (Twigg et al 2000;Williams et al 2007) and GonaCon improved body condition of deer (Gionfriddo et al 2011b). Conversely, Saunders et al (2002) observed no differences in survival, dispersal or territory size of surgically sterilised foxes compared with fertile foxes, although sterilised vixens were more likely than fertile females to share their territories with each other.…”
Section: Fertility-control Impact On Wildlife Populationsmentioning
confidence: 85%
“…When the size of a population is suddenly reduced, compensatory density-dependent processes may act to return the population to its previous level (Bomford 1990;Barlow 1994;Twigg et al 2000;Sinclair 2003;Ramsey 2005). In short-lived species, fecundity can make a greater proportional contribution than survival to population growth, and the reverse occurs in long-lived species (Sibly and Hone 2002).…”
Section: Fertility-control Impact On Wildlife Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first, molecular, immunological and reproductive biology studies commenced immediately to isolate and characterise rabbit reproductive antigens, initially sperm surface antigens, as candidates for gene cloning. Concurrently, studies were conducted in the field by surgically ligating the oviducts so that the rabbit's endocrine condition was not altered (Twigg et al 2000;Williams et al 2007). Further work continued to define…”
mentioning
confidence: 99%